Regimes of tonal noise on an airfoil at moderate Reynolds number. (4th September 2015) - Pröbsting, S.; Scarano, F.; Morris, S. C.
Abstract : Tonal noise generated by airfoils at low to moderate Reynolds number is relevant for applications in, for example, small-scale wind turbines, fans and unmanned aerial vehicles. Coherent and convected vortical structures scattering at the trailing edge from the pressure or suction sides of the airfoil have been identified to be responsible for such tonal noise generation. Controversy remains on the respective significance of pressure- and suction-side events, along with their interaction for tonal noise generation. The present study surveys the regimes of tonal noise generation for low to moderate chord-based Reynolds number between Re_c=0.3× 10^5 and 2.3× 10^5 and effective angle of attack between 0^° and 6.3^° for the NACA 0012 airfoil profile. Extensive acoustic measurements with smooth surface and with transition to turbulence forced by boundary layer tripping are presented. Results show that, at non-zero angle of attack, tonal noise generation is dominated by suction-side events at low Reynolds number and by pressure-side events at high Reynolds number. At smaller angle of attack, interaction between events on the two sides becomes increasingly important. Particle image velocimetry measurements complete the information on the flow field structure in the source region around the trailing edge. The influences of both angle of attack and Reynolds number on tonal noise generation are explained by changes in the mean flow topology, namely the presence and location of reverse flow regions on the two sides. Data gathered from experimental and numerical studies in the literature are reviewed and interpreted in view of the different regimes.